More than kings and less than men: tocqueville on the promise and perils of democratic individualism - Hebert, L. Joseph (New York, 2010)
More than Kings and Less than Men: Tocqueville on the Promises and Perils of Democratic Induvidualism examines Alexis de Tocqueville's hopes and fears for modern democracy, arguing that the distinctive political philosophy informing Democracy in America can help us to think more profoundly about the problems facing liberal democratic society today. L. Joseph Hebert, Jr. argues that Tocqueville saw the historical power of democracy as originating in its promise to liberate human nature, and the greatness it is capable of achieving, from the artificial constraints of conventional hierarchy. He probes Tocqueville's fear that the momentum of democratic change may violate that promise by neglecting or even stifling human greatness in the name of an artificial equality of conditions. Hebert explains why Tocqueville saw the need for a "new political science" to regulate democracy, and why Tocqueville thought that the central task of this science, supported by enlightened statesmanship, was to combat "individualism," an extreme form of civic, moral, and intellectual apathy capable of ushering in a historically unprecedented form of despotism. Hebert looks in depth at the principles of Tocqueville's political science, their relation to classical, modern, and contemporary political thought, and their practical applications in his time and ours. He outlines the model Tocqueville recommended for a free and flourishing modern democratic order and analyzes the primary mechanisms Tocqueville proposed for avoiding the perils and securing the promise of democracy in his own day. Hebert observes that many of Tocqueville's fears regarding individualism are occurring today, and analyzes how Tocqueville's insights might be applied to combat individualism and promote genuine liberty in our own time.
Keywords: Tocqueville, Alexis de,1805-1859-Political and social